Inovasi Kepala Sekolah dalam Peningkatan Kualitas Pendidikan di SMA Muhammadiyah Pontren Imam Syuhodo - Muhammad Nur Asy’ari; Nurul Latifatul Inayati (LP. Ma'arif Janggan Magetan, 2023)
Leadership is one of the important forces in achieving the goals of an educational institution. In the school environment, a person who is appointed to be a leader in the school environment is the principal. The principal as a leader has duties and responsibilities that he carries, including the principal must be able to guide, control, and direct his subordinates to carry out the tasks that are his responsibility. The principal is a role model, he must be at the forefront of various things, in terms of discipline, in terms of the term progressivity related to work. Besides that, which is no less important, now the principal is also an innovator. Namely, making updates, breakthroughs and innovations to develop the school he leads to achieve the goals he wants.